1992
DOI: 10.1002/j.1460-2075.1992.tb05108.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor I enhances adenovirus DNA replication by increasing the stability of a preinitiation complex.

Abstract: Nuclear factor I (NFI) or its isolated DNA‐binding domain (NFI‐BD) enhances initiation of adenovirus DNA replication up to 50‐fold at low concentrations of the precursor terminal protein‐DNA polymerase (pTP‐pol) complex. Both in solution and when bound to DNA, NFI‐BD can form a complex with pTP‐pol. To investigate the mechanism of enhancement by NFI, we determined the stability of a functional preinitiation complex formed in vitro between pTP‐pol and the origin. Challenge experiments with a distinguishable tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
74
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 64 publications
3
74
0
Order By: Relevance
“…The nuclear matrix is considered to be a scaffold to which the replication proteins are recruited. The nuclear matrix affinities of NF1 and OTF may also contribute to the increase in the stability of the PIC (39). The GR has also been shown to interact with the nuclear matrix (18,32).…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear matrix is considered to be a scaffold to which the replication proteins are recruited. The nuclear matrix affinities of NF1 and OTF may also contribute to the increase in the stability of the PIC (39). The GR has also been shown to interact with the nuclear matrix (18,32).…”
Section: Discussionmentioning
confidence: 99%
“…Three of these proteins are of viral origin: precursor terminal protein (pTP), polymerase (Pol), and DBP. pTP and Pol form a tight heterodimer in solution and bind to the origin located at the molecular ends of adenovirus DNA (23,28,31). Two other proteins, nuclear factor I (NFI) and Oct-1, originate from the host cell.…”
mentioning
confidence: 99%
“…The N terminus is able to stimulate adenovirus DNA replication by up to a factor of 50, and it has been shown that this stimulation does not require the NFI/CTF C terminus (9,11,12). NFI/CTF directly binds to the adenoviral DNA-polymerase, which is assumed to stabilize the preinitiation complex (13,14). 2 However, the cellular function of the NFI/CTF proteins has not yet been completely elucidated.…”
mentioning
confidence: 99%